High accuracy time-mode duty-cycle-modulation-based temperature sensor for energy efficient system applications - Zhu, Di (2015)
This paper presents a new time-mode duty-cycle-modulation-based high accuracy temperature sensor. Different from the well-known ΣΔADC based read-out structure, this temperature sensor's architecture utilizes a temperature-dependent oscillator to convert the temperature information into temperature related time-mode parameter, which means that the large power consumption of ΣΔADCs can be mitigated. The useful information of the oscillator's output is the duty-cycle, not the absolute frequency. In this way, a proportional to absolute temperature (PTAT) data stream is generated by the special oscillator. With a linear formula, this duty cycle stream can be converted into temperature value. The design is simulated in 0.18μm standard digital CMOS process. The simulation result shows that the worst temperature inaccuracy is kept within 0.5°C with a one-point calibration from -55°C to 125°C. The accuracy FOM is 0.185nJ%2.